2006
DOI: 10.1002/nau.20377
|View full text |Cite
|
Sign up to set email alerts
|

Detrusor overactivity and urge urinary incontinence following trans obturator versus midurethral slings

Abstract: Aims: To compare the rates of resolution of detrusor overactivity (DO) and subjective urge urinary incontinence (UUI) as well as de novo DO and UUI between the Monarc, TVT, and SPARC midurethral sling procedures. Methods: Two hundred and seventy-six subjects with urodynamic stress or mixed urinary incontinence underwent retropubic midurethral slings (TVT, N ¼ 99; SPARC, N ¼ 52) or transobturator slings (Monarc, N ¼ 125). All evaluable subjects had a routine o⁄ce evaluation, subjective assessment of UUI, and mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
51
0
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 88 publications
(58 citation statements)
references
References 15 publications
5
51
0
2
Order By: Relevance
“…Botros et al reported that the incidence of de novo DO was found in 33% of TVT, 8% of Monarc, and 17% of SPARC. Meanwhile, they also found that patients in the midurethral sling group had significantly lower rates of de novo DO than patients in the bladder neck sling group (29% vs 62%, P<0.05) [21,22]. In comparison, we had a relatively lower de novo DO rate (24%) than that of Botros et al Cardozo et al suggested that de novo DO is a result of nerve damage after bladder dissection and not necessarily a result of obstruction [23].…”
Section: Discussionmentioning
confidence: 51%
“…Botros et al reported that the incidence of de novo DO was found in 33% of TVT, 8% of Monarc, and 17% of SPARC. Meanwhile, they also found that patients in the midurethral sling group had significantly lower rates of de novo DO than patients in the bladder neck sling group (29% vs 62%, P<0.05) [21,22]. In comparison, we had a relatively lower de novo DO rate (24%) than that of Botros et al Cardozo et al suggested that de novo DO is a result of nerve damage after bladder dissection and not necessarily a result of obstruction [23].…”
Section: Discussionmentioning
confidence: 51%
“…This issue has been rarely ever reported other than by Deval et al, Falconer et al, and Botros et al. They briefly hypothesized that the changes in paraurethral collagen metabolism or sclerosis around the sling, or the effect position of the sling may elicit the new onset of urge symptoms [2,3,5].…”
Section: Introductionmentioning
confidence: 95%
“…Kim [12] conducted a prospective randomised trial of SPARC (n = 22) and Monarc (n = 21) surgeries, and reported similar short term cures rates (81.8% vs 80.9%) Botros [13] retrospectively compared Monarc (n = 125), Sparc (n = 52), and TVT (n = 99) slings and reported at 3 months the Monarc group had significantly less detrusor overactivity symptoms (8% vs 17% Sparcvs 33% TVT). This finding is similar to this present study.…”
Section: Discussionmentioning
confidence: 99%